Plan de negocios para la asociación artesanal de plantas medicinales la Laureñita del cantón Paltas, periodo 2023-2025. - Rodríguez Córdova, Andrea Carolina (2024)
Currently, in the parish of Lauro Guerrero, part of the canton of Paltas in the province of Loja, there is a significant demand for products made from medicinal plants, particularly horchata, which is renowned for its health benefits. Therefore, this graduation project focused on developing a business plan for the La Laureñita Artisanal Association of Medicinal Plants, with the objective of improving its profitability for the period 2023-2025. This plan proposed marketing and expansion strategies to increase the production and commercialization of medicinal plants, thereby promoting the growth of the artisanal association. Appropriate research methods were employed to analyze the market and determine the project's economic viability. As a result, the findings revealed a segment of young consumers interested in healthy and fair-trade products, which strengthens the association's value proposition. The financial analysis projected income growth if the proposed strategies are implemented, with a focus on strengthening the presence in digital channels. This business plan is expected to serve as a guide for the sustainable expansion of the La Laureñita Association in the medicinal plant market, allowing the company to achieve sustainable growth and position itself as a reference in the medicinal plant market, both locally and regionally, in the long term.